“The more things change, the more they stay the same”: Historicising mobility: Reading the Refugee Reception Crisis since 2015 through the Albanian Immigrant experience of 1991-2001 - Christopoulos, Dimitris; Karpozilos, Kostis; Spyropoulou, Georgia (The Historical Review/La Revue Historique, 2025)
This article challenges the dominant perception of the 2015 refugee crisis in greece as an unprecedented event by contextualising it within the country’s broader history of migration. Through a comparative analysis of two key episodes, the mass arrival of Albanian migrants in the 1990s and the post-2015 refugee presence, it demonstrates the continuities in state responses, public discourse and integration policies. drawing on legal, historical and sociopolitical perspectives, the study reveals how narratives of temporariness and “nonintegrability” have been consistently applied to newcomers, regardless of their background. While Albanian migrants were once vilified and later viewed as “successfully integrated”, today’s refugees are framed as transient and incompatible. The article critiques the failure of both national and EU policies to develop sustainable integration strategies, highlighting instead a shift towards exclusion and containment. it argues for the need to historicise mobility to understand contemporary migration beyond emergency framings.